Comparative study of Schistosomus Reflexus in production animals - Farias, Mayra da Silva; Costa, Caroline Pereira da (JRG Journal of Academic Studies, 2023)
Schistosomus reflexus (SR) is a rare congenital anomaly that affects various species of animals during the gestational period. The factors that characterize this disorder include the inversion of the vertebral column and the exposure of abdominal viscera resulting from a fissure in the abdominal wall. In addition, affected fetuses develop ankylosis and abnormal positioning of limbs, which are found adjacent to the skull. The stillbirths or abortions resulting from this condition have a considerable economic impact on the livestock industry. This study aims to provide a comprehensive analysis of Schistosomus reflexus in production animals, focusing on the congenital malformations resulting from this condition and its costly impact on the industrial environment, in order to compare SR across different species and identify similarities in their characteristics. This anomaly, mainly observed in cattle, can also affect small ruminants, buffaloes, pigs, and horses, resulting in significant deformities that are fatal to the fetus. Its etiology is considered idiopathic, as its exact cause is still unknown. The occurrence of this condition results in significant financial losses for producers, as affected animals have little or no commercial value and require investments to correct the effects resulting from the problem, such as dystocia in the parturient.